Translational neuroscience : toward new therapies - Nikolich, Karoly; Hyman, Steven E. (Strüngmann Forum reports., 2015)
Today, translational neuroscience faces significant challenges. Available therapies to treat brain and nervous system disorders are extremely limited and dated, and further development has effectively ceased. Disinvestment by the private sector occurred just as promising new technologies in genomics, stem cell biology, and neuroscience emerged to offer new possibilities. In this volume, experts from both academia and industry discuss how novel technologies and reworked translation concepts can create a more effective translational neuroscience. The contributors consider such topics as using genomics and neuroscience for better diagnostics and biomarker identification; new approaches to disease based on stem cell technology and more careful use of animal models; and greater attention to human biology and what it will take to make new therapies available for clinical use.